Complex training: The effect of exercise selection and training status on postactivation potentiation in rugby league players - Scott, D. J.; Ditroilo, M.; Marshall, P. A. (The Journal of Strength and Conditioning Research, 2017)
This study compared the postactivation potentiation (PAP) response of the hex bar deadlift (HBD) and back squat (BS) exercises. The PAP response between different levels of athletes was also compared. Ten professional and 10 amateur rugby league players performed 2 experimental sessions. Participants performed a countermovement jump (CMJ) before and 2, 4, 6, 8, 10, 12, 14, and 16 minutes after a conditioning activity (CA) that contained 1 set of 3 repetitions at 93% 1 repetition maximum of either HBD or BS. A force platform determined peak power output (PPO), force at PPO, velocity at PPO, and jump height of each CMJ. Surface electromyography (EMG) of the vastus lasteralis, rectus femoris, tibialis anterior, and gastrocnemius medialis of each participant's dominant leg was recorded during each CMJ. A further 10 participants performed a control trial without a CA. The HBD expressed PAP between 2 and 6 minutes post-CA, whereas the BS did not. The HBD exhibited a significantly (p = 0.05) greater PAP response than the BS for PPO. There were no significant (p > 0.05) differences between stronger and weaker players. There were no significant (p > 0.05) changes in the EMG variables. These results suggest that HBD is a suitable CA for eliciting PAP in stronger and weaker athletes. Strength and conditioning coaches should consider the CA and time frame between the CA and the plyometric exercise for optimal PAP responses.